2021
DOI: 10.1016/j.ebiom.2021.103254
|View full text |Cite
|
Sign up to set email alerts
|

BCG vaccination improves DTaP immune responses in mice and is associated with lower pertussis incidence in ecological epidemiological studies

Abstract: Background The Bacillus Calmette-Guérin (BCG), the only vaccine against tuberculosis (TB) currently in use, has shown beneficial effects against unrelated infections and to enhance immune responses to vaccines. However, there is little evidence regarding the influence of BCG vaccination on pertussis. Methods Here, we studied the ability of BCG to improve the immune responses to diphtheria, tetanus, and acellular (DTaP) or whole-cell pertussis (DTwP) vaccination in a mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…This rationale is based on our previous findings demonstrating that vaccination of mice with BCG or MTBVAC before vaccination with DTP results in higher antibody and Th1 responses than vaccination with DTP alone. Furthermore, exploration of human epidemiological data showed that pertussis incidence was 10-fold lower in countries that use DTP and BCG than in countries that use only DTP, supporting the hypothesis of a nonspecific immune enhancement of BCG favouring the DTP immune response [31] . Additionally, it is estimated that prevention of diphtheria, tetanus, and pertussis largely benefits from the 85% coverage of the different DTP vaccines available, and immunization with BCG against TB reached >90% vaccine coverage in 2019 [45] .…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…This rationale is based on our previous findings demonstrating that vaccination of mice with BCG or MTBVAC before vaccination with DTP results in higher antibody and Th1 responses than vaccination with DTP alone. Furthermore, exploration of human epidemiological data showed that pertussis incidence was 10-fold lower in countries that use DTP and BCG than in countries that use only DTP, supporting the hypothesis of a nonspecific immune enhancement of BCG favouring the DTP immune response [31] . Additionally, it is estimated that prevention of diphtheria, tetanus, and pertussis largely benefits from the 85% coverage of the different DTP vaccines available, and immunization with BCG against TB reached >90% vaccine coverage in 2019 [45] .…”
Section: Discussionmentioning
confidence: 81%
“…In addition to health benefits, the combination of multiple immunizations in a single vaccine allows lower costs in terms of production, distribution and personnel required for administration. We should also remember that live TB vaccines confer a plethora of beneficial, nonspecific effects [58] such as protecting against unrelated pathogens [18] , [22] through priming trained immunity [59] or enhancing the immunity of unrelated vaccines [31] . Taken together, these heterologous effects of live TB vaccines together with the potential to construct recombinant derivatives open exciting perspectives for next-generation vaccine strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MTBVAC is in phase II clinical trial and demonstrated protection of mice [37] and rhesus macaques against M. tuberculosis aerosol challenge [38]. Previous immunization with MTBVAC can also enhance the immune response in synergy with the pertussis vaccine [39], while having the same capacity as BCG to induce innate memory [40].…”
Section: Discussionmentioning
confidence: 99%
“…The non-target benefit of BCG may be most pronounced when the BCG vaccine is administered after non-live vaccines, as suggested in a secondary analysis from India that found that children who received BCG and diphtheria-tetanus-pertussis (DTP) vaccines at the same time or BCG after DTP experienced lower mortality at one year of age [21]. A global ecologic study suggests that pertussis incidence is substantially lower in countries with immunization programs that administer both BCG and diphtheria-tetanus-acellular pertussis (DTaP) vaccines compared to those that do not give BCG [22]. Indeed, some authors have suggested that discontinuing live vaccine administration after disease eradication could have unintended effects due to the loss of non-specific protection [23].…”
Section: Bcg Trained Immunity and Clinical Infectionmentioning
confidence: 99%